2022
DOI: 10.3390/antibiotics11070834
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Biogenic Silver Nanoparticles from Syzygium aromaticum against the Five Most Common Microorganisms in the Oral Cavity

Abstract: Syzygium aromaticum (clove) has been used as a dental analgesic, an anesthetic, and a bioreducing and capping agent in the formation of metallic nanoparticles. The main objective of this study was to evaluate the antimicrobial effect in oral microorganisms of biogenic silver nanoparticles (AgNPs) formed with aqueous extract of clove through an ecofriendly method “green synthesis”. The obtained AgNPs were characterized by UV-Vis (ultraviolet-visible spectroscopy), SEM-EDS (scanning electron microscopy–energy di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…Recently, another study proved antifungal activity of a hydroethanolic extract from Astronium urundeuva leaves loaded into a nanostructured lipid system with 0.5% P407 ® against C. albicans and C. glabrata [ 95 ]. Previous studies [ 96 , 97 ] included the most common oral cavity pathogens responsible for various opportunistic infections in immunocompromised patients, S. aureus , P. aeruginosa , and C. albicans. Our F-UBO oral biofilms revealed a dose-dependent inhibitory activity against S. aureus , P. aeruginosa , C. albicans , and C. parapsilosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another study proved antifungal activity of a hydroethanolic extract from Astronium urundeuva leaves loaded into a nanostructured lipid system with 0.5% P407 ® against C. albicans and C. glabrata [ 95 ]. Previous studies [ 96 , 97 ] included the most common oral cavity pathogens responsible for various opportunistic infections in immunocompromised patients, S. aureus , P. aeruginosa , and C. albicans. Our F-UBO oral biofilms revealed a dose-dependent inhibitory activity against S. aureus , P. aeruginosa , C. albicans , and C. parapsilosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we evaluated the UBA antimicrobial potential on bacterial and fungal strains responsible for opportunistic oral cavity infections in elderly and/or immunocompromised patients [ 78 , 79 , 80 ]: S. aureus , S. pneumoniae , S. pyogenes , Enterococcus sp., other Gram-positive bacteria isolated from oral cavity and pharynx ( S. epidermidis , S. oralis , S. intermedius ) and P. aeruginosa [ 34 , 81 , 82 , 83 ]. It was also tested on C. albicans and C. parapsilosis [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because OSCC decreases immune defense, the oral cavity becomes more susceptible to bacterial and fungal infections. Therefore, UBA-loaded mucoadhesive oral films could inhibit S. aureus , P. aeruginosa , and Candida sp., which are responsible for opportunistic oral infectious diseases in immunocompromised patients [ 78 , 79 ]. These results proved the chemotherapeutic effect of UBA-loaded mucoadhesive oral films.…”
Section: Discussionmentioning
confidence: 99%
“…In their previous studies, Jardón-Romero et al [ 104 ], Rafey et al [ 105 ], and Thiyahuddin et al [ 106 ] considered S. aureus, P. aeruginosa, C. albicans, and C. parapsillosis as the most frequent pathogens responsible for opportunistic oral cavity infections in immunocompromised and older people; we previously examined UBE inhibitory activity against these microbial species [ 90 ]. Our results showed that oral mucoadhesive patches loaded with U. barbata dry ethanol extract have a dose-dependent inhibitory activity against these microorganisms.…”
Section: Discussionmentioning
confidence: 99%